Syria's economy and the transition paradigm - Abboud, Samer (St. Andrews papers on contemporary Syria, 2009)
Exploring the recent trajectory of Syria's economy, the authors consider the utility of the transition paradigm - developed to study change in the former communist states - as an explanatory approach." "In the first part of the book, Samer Abboud examines Syria's shift to a "social market economy," focusing on similarities in and differences between the Syrian and Chinese cases. In the second part, Ferdinand Arslanian compares empirical indicators for Syria with those from the aggregate of transition countries to predict Syria's economic performance and the rate of liberalization. A foreword by Raymond Hinnebusch provides context for the study.